Terminology and forensic gait analysis. Issue 4 (July 2015) - Birch, Ivan; Vernon, Wesley; Walker, Jeremy; Young, Maria
Abstract: The use of appropriate terminology is a fundamental aspect of forensic gait analysis. The language used in forensic gait analysis is an amalgam of that used in clinical practice, podiatric biomechanics and the wider field of biomechanics. The result can often be a lack of consistency in the language used, the definitions used and the clarity of the message given. Examples include the use of 'gait' and 'walking' as synonymous terms, confusion between 'step' and 'stride', the mixing of anatomical, positional and pathological descriptors, and inability to describe appropriately movements of major body segments such as the torso. The purpose of this paper is to share the well-established definitions of the fundamental parameters of gait, common to all professions, and advocate their use in forensic gait analysis to establish commonality. The paper provides guidance on the selection and use of appropriate terminology in the description of gait in the forensic context. This paper considers the established definitions of the terms commonly used, identifies those terms which have the potential to confuse readers, and suggests a framework of terminology which should be utilised in forensic gait analysis.